Battlefield monuments and popular historicism: a hermeneutic study of the aesthetic encounter with 'Waterloo'. Issue 4 (2nd October 2022) - Gilks, Mark
ABSTRACT: Focusing on the case of the tourist visiting battlefield monuments at Waterloo, this article explores how war is historicized in the public imagination through the monumentalization of objects. The argument is two-fold. Firstly, drawing on Gadamer's hermeneutics, it is argued that 'tradition' is constituted in the aesthetic encounter between tourist and monument (as subject and object); such encounters are therefore understood as the genesis of historical meaning. Secondly, through a critique of Gadamer's notion of ontological structures of meaning, it is argued that the tourist is phenomenologically implicated in the constitution of historical meaning, emphasizing the agency of the historical observer more than Gadamer allows for: Objects become monuments through the monumentalizing gaze of the tourist. To empirically illustrate these processes, the author ethnographically explores the experience of battlefield tourist and presents his own dialogue with war-tradition at Waterloo. As such, this study contributes a theoretical account of how war is historicized at the phenomenological level, which has broader sociological implications for understanding how war discourses originate and are sustained in the public imagination.